2017
DOI: 10.1016/j.biochi.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

From fat to FAT (CD36/SR-B2): Understanding the regulation of cellular fatty acid uptake

Abstract: The molecular mechanisms underlying the cellular uptake of long-chain fatty acids and the regulation of this process have been elucidated in appreciable detail in the last decades. Two main players in this field, each discovered in the early 1990s, are (i) a membrane-associated protein first identified in adipose ('fat') tissue and referred to as putative fatty acid translocase (FAT)/CD36 (now officially designated as SR-B2) which facilitates the transport of fatty acids across the plasma membrane, and (ii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(112 citation statements)
references
References 65 publications
6
104
1
Order By: Relevance
“…In this sense, the intracellular transport of free FAs in mammals is facilitated by specific low-molecularweight and highly conserved cytoplasmic proteins that bind both long-chain FAs and other hydrophobic ligands. These fatty acid binding proteins (FABPs) are tissue specific and those from the liver, intestine, adipose tissue, brain and heart have been characterized extensively in mammals (Glatz and Luiken 2017). Similar studies have been reported in different fish species (Tocher 2003).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In this sense, the intracellular transport of free FAs in mammals is facilitated by specific low-molecularweight and highly conserved cytoplasmic proteins that bind both long-chain FAs and other hydrophobic ligands. These fatty acid binding proteins (FABPs) are tissue specific and those from the liver, intestine, adipose tissue, brain and heart have been characterized extensively in mammals (Glatz and Luiken 2017). Similar studies have been reported in different fish species (Tocher 2003).…”
Section: Introductionsupporting
confidence: 53%
“…(Jump 2004; reviewed by Glatz and Luiken 2017). Initially, it was considered that LCFAs were taken up by cells through passive diffusion mechanisms (Kamp et al 2003;Pownall and Hamilton 2003;Hamilton and Brunaldi 2007), while evidence has shown that LCFA uptake is also facilitated by a proteinmediated mechanism Bonen et al 2007;Guo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the vast majority of carbons contributing to the intracellular lipid pool in BrCa cells arise from extracellular FAs and not from glucose or glutamine (Balaban et al ., 2017). Cells take up FAs from the bloodstream or local microenvironment via various surface transport proteins (Glatz and Luiken, 2017). FAs are then condensed into and stored as TAG in lipid droplets (Farese and Walther, 2009) and other complex lipids including phospholipids (Louie et al ., 2013), or enter the mitochondria for β‐oxidation (Bruce et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids, glycerol, and monoacylglycerols are important precursors for their synthesis and are obtained from two sources. First, these precursors are taken up by cells from the extracellular environment via transporters present on the plasma membrane, such as CD36 and fatty acid transport proteins (10; [19][20][21], and are carried by cytoplasmic proteins, e.g., fatty acid-binding proteins (10;22), from the plasma membrane to the ER. Second, these precursors can be generated intracellularly after the hydrolysis of lipids stored in cytoplasmic lipid droplets (cLDs).…”
Section: Synthesis and Mobilization Of Lipids For Lipoprotein Assemblymentioning
confidence: 99%